Bending and buckling analysis of functionally graded plates using a new shear strain function with reduced unknowns / Ali Meftah - Meftah, Ali (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
In this article, functionally graded plates' buckling and bending analyses are investigated using a new shape function. The parabolic transverse shear stresses throughout the thickness are regarded by this function as meeting the shear stress-free surface conditions and enabling an accurate distribution of shear deformation according to the thickness of the plate without integrating shear correction factors. Compared to previous shear theories, this higher-order shear theory has the fewest unknowns. The equations for the functionally graded plates are produced by employing the Hamiltonian principle, and the solutions are obtained using Napier's technique. The outcomes of the current analysis are provided and contrasted with those found in the literature.